Do Environmental Practices Improve Business Performance Even in an Economic Crisis? Extending the Win-Win Perspective - Seles, Bruno Michel Roman Pais [UNESP]; Lopes de Sousa Jabbour, Ana Beatriz; Jabbour, Charbel Jose Chiappetta; Latan, Hengky; Roubaud, David (Elsevier, 2019)
This article analyses the effects of economic crises on the relationship between environmental practices, environmental performance and business performance. Six hypotheses are tested via survey responses from firms located in Brazil – a country that has recently faced a serious economic crisis. The data were analysed using PLS path-modelling (PLS-PM). The findings are discussed through the theoretical lenses of contingency theory and dynamic capabilities theory. We provide evidence that the aftermath of the recent economic crisis has significantly weakened the relationship between environmental practices, environmental performance and business performance among Brazilian firms. However, environmental practices that are linked to firms' strategy and have dynamic capability characteristics can still improve business performance, even under economic contingencies, as the win-win characteristics of these practices remain even in times of economic crisis. Firms may benefit from the awareness that even in difficult times, environmental practices continue to support business performance. The article extends the understanding of the ‘win-win situation’ regarding a market environment facing an economic crisis. The originality of this study, to the best of our knowledge, is that it is the first study to employ this theoretical and methodological approach to deal with this key societal and economic subject.
Keywords: Business Performance; Economic Crisis; Environmental Performance; Environmental Practices